KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA SEKOLAH MELALUI MANAJEMEN BERBASIS SEKOLAH - Hernita, Rika (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
This research investigated headmasterâs strategy to develop schoolâ culture through School Based Management. It used a qualitative approach with case studies. Data were collected by using interviews, observation, and study of the documents/artifacts. Data validation was done through credibility, transferability, dependability, and confirmability. This results showed that headmasterâs strategy to develop schoolâ culture started from developing discipline culture.